Analisis Break Event Point Pada UMKM Ayam Geprek Pak Iwan - Mohamad Bastomi; Erda Dwi Ananda Asyadi; Sesarini Rahma Indahsari; Nurul Iffatil Azizah (DPPM Universitas Pelita Bangsa, 2022)
An entrepreneur has a main goal in running his business, which is to get a lot of profit or profit. In addition to getting more profit from sales, there must be a phase when profits rise and fall. If there is a decrease in profit or profit, an entrepreneur can change the pattern in running his business so that profits or profits can stabilize again and not experience excessive losses. This research focuses on the Break Even Point analysis of the Tata Surya Geprek Chicken business, Dinoyo. The research method we use is a qualitative method of literature review and interviews. From the results of research conducted at Mr. Iwan's Ayam Geprek UMKM on Jalan Tata Surya, using multi-product BEP, it was found that the BEP point for geprek chicken and rice products in units of 312 units or in rupiah of Rp 3,395,000, BEP for teriyaki sauce chicken products in units of 270 units or in rupiah of Rp 1,264,000, and BEP for original geprek chicken in units of 334 units or in rupiah of Rp 2,264,000. These results can be used as a reference for MSME owners to plan production capacity or minimum sales targets.